Evaluation of Cellular Response to 3D-Printed Scaffolds Based on Polyhedral Geometries: Icosahedron, Dodecahedron, and Truncated Icosahedron - Cruz-Maya, Iriczalli (2026)
Tissue engineering has increasingly focused on developing scaffolds capable of providing structural support while promoting cell adhesion and distribution on the scaffold surface, thereby supporting tissue regeneration. In this study, polyhedral-based scaffolds with dodecahedron, icosahedron, and truncated icosahedron geometries were designed and fabricated from polylactic acid (PLA) using fused deposition modeling (FDM) 3D printing. The morphology and pore size of the scaffolds were characterized using optical microscopy, and their mechanical behavior was evaluated through uniaxial compression tests in flat and vertical orientations. Human gingival fibroblasts (HGF) were cultured on the scaffolds to evaluate cell proliferation using WST-1 assays after 1, 3, and 7 days, as well as cell morphology and distribution by scanning electron microscopy (SEM) and fluorescence microscopy after 24 h. Statistical analysis was performed using one-way analysis of variance (ANOVA) followed by Tukey’s post hoc test (p<0.05). The results demonstrated that the scaffold geometry and loading orientation significantly influenced the mechanical behavior of the printed structures. The vertically oriented icosahedron scaffold exhibited the highest compressive strength (378.45±0.09 MPa), whereas the truncated icosahedron exhibited the highest elastic modulus (147.07±2.13 MPa). HGF proliferation remained comparable to that of the tissue culture plate control over the evaluated time periods. SEM and fluorescence microscopy revealed cell adhesion and distribution on all scaffold surfaces, although differences in cell organization were observed depending on the scaffold geometry. The results indicate that polyhedral architectures influence both the mechanical properties and cellular response of 3D-printed PLA scaffolds.